Treatment of the textile wastewater using Malaysian Ganoderma lucidum mycelial pellets - Hanafiah, Zarimah Mohd; Azmi, Ammar Radzi; Ilham, Zul; Wan Mohtar, Wan Hanna Melini; Halim-Lim, Sarina Abdul; Nafisyah, Ayu Lana; Show, Pau-Loke; Wan-Mohtar, Wan Abd Al Qadr Imad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Purification of textile wastewater using biomass and in particular different fungi is gaining exponential interest to minimize the impacts of current physical-chemical and biological wastewater treatment by-products. This study investigates the potential of Malaysian Ganoderma lucidum mycelium pellets (GLMP) for the decontamination of wastewater samples received from a commercial textile manufacturer. All studies were performed under ambient temperature (26-35 ℃) and unsterilized conditions using a simple bioreactor design (stirred batch bioreactor) for a more practical assimilation of the current available wastewater treatment process system. The optimal conditions of adsorption by GLMP were determined by variation effects of adsorbent concentration (0, 8.75, 12.5 and 25 g/L), pH (unadjusted 7.10 – 8.22, 4 and 6), and wastewater dilution factor (1:0, 1:4, and 2:3, v/v). This method was proved to be effective in both decolorization and chemical oxygen demand (COD) reduction, simultaneously. The most significant percentage of decolorization observed was 77.24% in a 72 h treatment, whereas COD reductions were 78.32% in a 36 h treatment. The present study fits both Langmuir and Freundlich adsorption isotherms as the values of R2 both model were close to 1, indicating the favorable adsorption of dyes towards Malaysian GLMP.